Соматоформная вегетативная дисфункция: эволюция диагноза и подходов к лечению, традиционная и современная физиотерапия - Васильева-Линецкая, Лариса Яковлевна (Видавництво "Факт", 2018)
У статті надана сучасна класифікація соматоформних розладів, а також основні клінічні варіанти соматоформної вегетативної дисфункції, її етіопатогенез і типи перебігу. Обґрунтовано значення мультидисциплінарного лікування і реабілітації, викладені основні принципи психотерапії та фармакотерапії. Проведено аналіз диференційованого впливу основних методів класичної і сучасної фізіотерапії, показана висока ефективність застосування сучасної фізіотерапії для лікування та реабілітації хворих з соматоформною вегетативною дисфункцією з позицій доказової медицини. Викладено диференційовані покази для використання методів класичної фізіотерапії при реабілітації хворих.

Up-to-date classification of somatic symptom disorders as well as basic clinical variants of somatic autonomic disorder, its aethiopathogenesis and treatment methods are listed. Importance of multidisciplinary treatment and rehabilitation is proved, basic principles of psychotherapy and medication therapy are described. Differential influence of basic modalities of conventional and contemporary physical medicine is analyzed, high efficiency of contemporary physical therapy in treatment and rehabilitation of patients with somatic autonomic disorder from the viewpoint of evidence-based medicine is discussed. Differential indications for conventional physical medicine methods application in patient rehabilitation are listed.
Somatic autonomic disorder: evolution of diagnosis and treatment approach, traditional and contemporary physical medicine
Keywords: соматоформні розлади; соматоформна вегетативна дисфункція; психотерапія; медикаментозна терапія; класична та сучасна фізіотерапія; somatic symptom disorder; somatic autonomic disorder; psychotherapy; medication therapy; physical medicine